KEMAMPUAN BERPIKIR KREATIF SISWA SMP KELAS VIII PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL MELALUI PENDEKATAN OPEN ENDED - Anggraeni, Inggri; Zanthy, Luvy Sylviana; Hendriana, Heris (IKIP Siliwangi, 2018)
This study aims to examine the improvement of student’s creative thinking ability of Class VIII on the material of two-variable linear equation system through open ended approach. This type of research is classroom action research. The method of this research is qualitative descriptive. This research was conducted on grade VIII-C student of SMP Darul Falah in the academic year 2017/2018 with 36 student. The instrument used in a student’s mathematical creative thinking test, cycle I and II test (after giving of action), and an observation sheet for teachers and students to conditions of action implementation. The result of this study indicate that the aspect of matehematical thinking creative ability of students has increased because of the problems tested in each test, the more students who score above the KKM. Based on the work indicator, it is concluded that the mathematical creative thinking ability of grade VIII-C students of SMP Darul Falah on two-variable linear equation system can be improved through open ended approach.